Modelling and assessing public health policies to counteract Italian measles outbreaks. (3rd November 2021) - Scirè, Giovanni
This study aims to understand, through explanatory research, the key factors that led to the 2017 measles outbreak in Italy, the causes of the low level of immunisation and the causes of possible cyclical phenomena of measles epidemics. This topic's comprehension has required a holistic approach, merging epidemiological aspects, socioeconomic aspects (including the evolution of mistrust in vaccinations, infodemy and fake news) and health law constraints. A specific SIR system dynamics (SD) model was built to reproduce the relevant cause-and-effect relationships between social interactions, the public institutions' behaviour and the measles outbreaks. SD results permit the assessment of the health policies to counteract the measles outbreaks. Findings, limits and further research recommendations are briefly reported in the conclusions.